Three-Dimensional Numerical Analysis of Dowel-Type Connections in Timber Engineering - Kaliske, Michael (Springer, 2017)
Dowel-type connections of wood are characterized by a complex load-bearing behavior and failure mechanism. For prediction and understanding of this behavior, numerical simulations of double shear dowel-type connections are intro-duced. The failure of the wood components and the steel fasteners are modeled and appropriate material formulations are introduced. The analysis of the numeri-cal calculation and verification shows the suitability of the model to predicting the load-carrying capacity and the failure mechanism.